Macroeconomic Policy Frameworks for Resource-Rich Developing Countries : Analytic Frameworks and Applications. (Policy Papers; Policy Paper, 2012)
This supplement presents the analytical frameworks underlying the IMF's staff's enhanced policy analysis and advice to resource-rich developing countries (RRDCs). The proposed macro-fiscal models, which are applied to selected country or regional cases, are aimed at addressing questions regarding how to deal with resource revenue uncertainty and how to scale up spending within relevant frameworks that ensure fiscal and external sustainability while addressing absorptive capacity constraints. The country applications confirm the importance attached by both IMF staff and country authorities of using the appropriate macro-fiscal frameworks to address the specific challenges faced by RRDCs.